Towards a re-imagined notion of university education: In defence of a reconstituted ethics of care - Shanyanana, Rachel Ndinelao; Waghid, Yusef (South African Journal of Higher Education, 2018)
This article argues that women on the African continent experience moments of internal exclusion in higher education institutions. Although women are statistically represented — attaining external inclusion in minimal ways — they remain subjected to internal exclusion on the grounds that their contributions are evidently unsubstantive. Through a conceptual analysis of women’s experiences of African higher education, the article reveals that internal exclusion can be attributed to a gendered view of equality, mostly generated in people’s social, political and cultural practices. I contend that an equalisation of voice rather than gender may possibly disrupt the status quo and undermine the debilitating conditions that perpetuate women’s internal exclusion on the continent. By examining the implications of a reconstituted ethics of care for university education, the article offers some ways in which exclusionary practices can be remedied. This article contends that, if higher education in Africa (university education) were to halt the dilemma of internal exclusion and move towards engendering a reconstituted ethics of care, then it stands an authentic chance of cultivating compassionate, imaginative and responsible citizens who can reason, not only for themselves, but for humanity as well.